Decreased Npas4 and Arc mRNA Levels in the Hippocampus of Aged Memory‐Impaired Wild‐Type But Not Memory Preserved 11β‐HSD1 Deficient Mice. (17th January 2016) - Qiu, J.; Dunbar, D. R.; Noble, J.; Cairns, C.; Carter, R.; Kelly, V.; Chapman, K. E.; Seckl, J. R.; Yau, J. L. W.
Abstract : Mice deficient in the glucocorticoid‐regenerating enzyme 11β‐HSD1 resist age‐related spatial memory impairment. To investigate the mechanisms and pathways involved, we used microarrays to identify differentially expressed hippocampal genes that associate with cognitive ageing and 11β‐HSD1. Aged wild‐type mice were separated into memory‐impaired and unimpaired relative to young controls according to their performance in the Y‐maze. All individual aged 11β‐HSD1‐deficient mice showed intact spatial memory. The majority of differentially expressed hippocampal genes were increased with ageing (e.g. immune/inflammatory response genes) with no genotype differences. However, the neuronal‐specific transcription factor, Npas4, and immediate early gene, Arc, were reduced (relative to young) in the hippocampus of memory‐impaired but not unimpaired aged wild‐type or aged 11β‐HSD1‐deficient mice. A quantitative reverse transcriptase‐polymerase chain reaction and in situ hybridisation confirmed reduced Npas4 and Arc mRNA expression in memory‐impaired aged wild‐type mice. These findings suggest that 11β‐HSD1 may contribute to the decline in Npas4 and Arc mRNA levels associated with memory impairment during ageing, and that decreased activity of synaptic plasticity pathways involving Npas4 and Arc may, in part, underlie the memory deficits seen in cognitively‐impaired aged wild‐type mice.